Effects of Benzo(a)pyrene on the endometrial receptivity and embryo implantation in mice: An experimental study - Zeinab Mardanshahi; Abbasali Karimpour Malekshah; Fereshteh Talebpour Amiri; Reza Valadan (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Benzo(a)pyrene (BaP) as an environmental pollutant is ubiquitous in the environment and it has destructive effects on human health. So far, various studies have demonstrated that BaP can cause adverse effects on the female reproductive system, but the existing information is limited about the effects of BaP on the endometrial receptivity and embryo implantation. Objective: The aim of this study was to investigate the effects of BaP on the endometrial receptivity and implantation in mice. Materials and Methods: In this experimental study, 40 pregnant BALB/c mice were divided into 5 groups (n = 8/each) as follows: experimental groups received the doses of 100 μg/kg, 200 μg/kg, and 500 μg/kg BaP dissolved in corn oil, the control group received normal saline and sham group received corn oil. Pregnant mice administered these solutions from Day 1 to Day 5 of gestation by gavage. On Day 6, the mice were sacrificed. Then their embryos were counted and the hormonal, histomorphological and molecular analyses were performed on themocusa of uterine tube. Results: The data revealed that BaP reduces estrogen and progesterone levels, decreases the number of implantation site, endometrium thickness, uterine lumen diameter, stromal cells and endometrial glands, and blood vessels in the endometrium. However, the expression of Activin receptor-like kinase 5 and E cadherin genes was not changed by BaP with different doses. Conclusion: The finding of this study showed that BaP can change estrogen and progesterone levels, and endometrial morphology leads to impairing the endometrial receptivity and decreasing the number of implantation site.